Water Content, Total Dissolved Solids and Antioxidant Activity of Robusta Coffee Powder Produced by Fermenting Beans in Whey Kefir - Priyo Bintoro; Anggun Miftahurrahmi; Heni Rizqiati (Diponegoro University, 2023)
Coffee is one of the plantation commodities that is usually processed into beverage products. The most widely cultivated coffee in Indonesia is Robusta coffee. However, Robusta coffee has a lower quality compared to other types of coffee. Fermentation of coffee beans during wet processing can improve coffee quality. The purpose of this study was to determine the best fermentation time for robusta coffee beans in whey kefir so that quality robusta coffee powder was obtained from the water content, total dissolved solids (TDS) and antioxidant activity. This study used a completely randomized design (CRD) with different fermentation time treatments. Parametric data were analysed by ANOVA and followed by DMRT test. Antioxidant activity data were analysed descriptively. Longer fermentation times reduced the total dissolved solids (TDS) of the coffee beans. However, prolonged fermentation can also increase the water content and reduce antioxidant activity. The best treatment was found to be a fermentation time of 18 hours, which resulted in a coffee bean with a good balance of TDS (3.25°Brix), water content (4.67%), and antioxidant activity (16.09 ppm).